EVALUATION OF PATIENT SAFETY REPORTING SYSTEM AT TUBAN HOSPITAL - Muhammad Sudrajad; Miftahul Munir (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Background: The incident reporting system is designed to obtain information about patient safety which is used for organizational and individual learning. Objective: The purpose of the study was to evaluate the implementation of a patient safety incident reporting system in hospitals. The research is in the form of observational descriptive supported by qualitative data. The evaluation in this study used the Health Metrics Network (HMN) model. Results: The results of the evaluation of the patient safety incident reporting system at a hospital in Surabaya indicate that in terms of input there has been a policy that regulates patient safety incident reporting but unfortunately the implementation of this policy is still not appropriate, there is no direct funding but facilities are provided for In making reports, officers have been given socialization but there are differences in understanding and sense of responsibility of officers, the organizational structure of the patient safety team already exists, problem solving methods have not used PDSA (Plan, Do, Study, Action), the technology used is computerized. Conclusion: Evaluation in terms of process, indicators are in accordance with regulations, data sources are in accordance with patient safety incident guidelines and guidelines, and collection, processing, presentation, and analysis are in accordance with theory. Evaluation in terms of output, submission of incident reports has not been on time, reports are complete and in accordance with existing guidelines, and reports have been used for decision making. Hospitals are expected to improve incident reporting guidelines and improve human resource capabilities.